Strengthening the Competence of Community-Based Water Tourism Guides to Support Sustainable Tourism - Anak Agung Ayu Ribeka Martha purwahita; Auzan Tawadlu Akbar; Rizki Sumardani (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to analyze the strengthening of human resource competencies among community-based water tourism guides in supporting sustainable tourism. It focuses on the strategic role of guides in ensuring visitor safety, environmental preservation, and enhancing the welfare of local communities within the framework of community-based tourism. Method: This research employs a qualitative approach with a descriptive design. The study was conducted in a community-based water tourism destination. Data were collected through field observations, in-depth interviews with water tourism guides, destination managers, and relevant stakeholders, as well as document analysis. The data were analyzed using qualitative descriptive techniques, including data reduction, data display, and conclusion drawing, to obtain a comprehensive understanding of guide competencies and the strategies implemented to enhance them. Result: The findings reveal that strengthening the competencies of water tourism guides must be conducted continuously through structured education, training, and standardized certification. Key competency areas requiring improvement include technical skills, occupational health and safety, and interpersonal abilities. Additionally, active community involvement in tourism management contributes to improved service quality, reduced accident risks, and stronger sustainability outcomes, while also generating economic benefits for local communities. Contribution: This study contributes to the growing body of knowledge on sustainable and community-based tourism by highlighting the critical role of human resource competency development in high-risk tourism activities. It provides practical insights for policymakers, destination managers, and training institutions to design more effective capacity-building programs. Furthermore, the findings offer a framework for integrating safety, sustainability, and community empowerment, thereby supporting the long-term development of water tourism destinations.